Surgical management for large chest keloids with internal mammary artery perforator flap - Dan Xue; Huan Qian (Sociedade Brasileira de Dermatologia, 2016)
Abstract Therapy for large symptomatic keloids is often plagued with complicated reconstruction manner and recurrence. This article reports a rare treatment combination for a chest keloid with internal mammary artery perforator flap reconstruction and radiation therapy. We excised the keloid and covered the defect with an internal mammary artery perforator flap. Immediate electron-beam irradiation therapy was applied on the second postoperative day. There was no sign of recurrence over the follow-up period of 18 months. The combination of internal mammary artery perforator flap and immediate radiation therapy is useful when faced with chest keloids of similar magnitude and intractability.